IMPLEMENTASI DIGITALISASI LAYANAN BIDANG PELAYANAN ANGKUTAN MELALUI APLIKASI SIMAE DI DINAS PERHUBUNGAN KOTA BOGOR - Hasibuan, Ilal Hamdi; Santoso, Hudi (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2025)
This study examines the implementation of the SIMAe application (Electronic Transportation Management Information System) as a form of digital public service transformation at the Department of Transportation of Bogor City, particularly in the transportation services division. The primary aim is to understand the benefits, challenges, and impacts of using SIMAe on service efficiency. A qualitative approach was employed, using observation, interviews, and document analysis conducted during the author’s internship at the research location. The findings show that SIMAe significantly improves licensing efficiency, reducing service processing time from several days to just minutes, and enhances transparency through real-time tracking of licensing status. Additionally, the system significantly reduces the use of physical documents, lowers operational costs, and supports sustainability principles. However, major challenges include inadequate digital infrastructure and low digital literacy among staff and the public. The continued reliance on manual systems also hinders the full optimization of SIMAe. Nevertheless, with continuous improvement and proper training, SIMAe has great potential to become a successful model for digital public service delivery that is efficient, transparent, and environmentally friendly in Indonesia